Sociologin i Grekland: från 1907 fram till Metaxas-diktaturen (1936–1940) och andra världskriget (Sociologisk Forskning, 2012)
Sociology in Greece from 1907 to the Metaxas dictatorship (1936–40) and the Second World War This paper focuses on pre-conditions for sociology to develop and the subject matters of emerging sociology in Greece. Pre-conditions were at hand but without continuity, and the opportunity for sociology to develop was lost. Sociology is said to have started in 1907 with the book The Social Question by Georgos Skliros. He presented sociology and Marxism as identical and deals with Greek society and (among other things) the language issue, all of which triggered off a vibrant debate. Sociological associations and journals were started. However, the initially reformist perspective of social science was gradually replaced by an approach that was more socio-philosophical, influenced by classical sociology, German sociology in particular. This turn was associated with the institutionalization of sociology at the universities during the 1920’s. The Metaxas dictatorship in 1936 put a stop to any further development of sociology for a long time.